A new vesicle trafficking regulator CTL1 plays a crucial role in ion homeostasis - Gao, Yi-Qun; Chen, Jiu-Geng; Chen, Zi-Ru; An, Dong; Lv, Qiao-Yan; Han, Mei-Ling; Wang, Ya-Ling; Salt, David E.; Chao, Dai-Yin (Public Library of Science, 2017)
Ion homeostasis is essential for plant growth and environmental adaptation, and maintaining ion homeostasis requires the precise regulation of various ion transporters, as well as correct root patterning. However, the mechanisms underlying these processes remain largely elusive. Here, we reported that a choline transporter gene, CTL1, controls ionome homeostasis by regulating the secretory trafficking of proteins required for plasmodesmata (PD) development, as well as the transport of some ion transporters. Map-based cloning studies revealed that CTL1 mutations alter the ion profile of Arabidopsis thaliana. We found that the phenotypes associated with these mutations are caused by a combination of PD defects and ion transporter misregulation. We also established that CTL1 is involved in regulating vesicle trafficking and is thus required for the trafficking of proteins essential for ion transport and PD development. Characterizing choline transporter-like 1 (CTL1) as a new regulator of protein sorting may enable researchers to understand not only ion homeostasis in plants but also vesicle trafficking in general.